Atividades educacionais desenvolvidas no Brasil para profissionais e graduandos em saúde com foco em segurança do paciente: Scoping review - Vieira, Vanisia Sulpino (Universidade Federal de São Carlos, 2023)
Theoretical debates on patient quality and safety have been widely discussed, but fewer studies have focused on educational activities for healthcare professionals in this context. The training of these professionals is essential in promoting safe care and preventing adverse events. Investing in patient safety education is a strategy to achieve harm-free healthcare. However, healthcare services face challenges in implementing the National Patient Safety Program and ensuring quality care. Therefore, it is important to identify the scientific literature that evidences the state-of-the-art educational activities for patient safety. Objective: The objective of this study is to map and present the scientific literature on educational activities focused on patient safety, developed with healthcare professionals and undergraduate students in Brazil. The basic themes of the National Patient Safety Program will be considered. This will be done through a scope review. Methods: The theoretical frameworks were selected through a literature review, following the scoping review method and the protocol of the Joanna Briggs Institute. The consulted databases included the National Library of Medicine (PubMed), the Latin American and Caribbean Center on Health Sciences Information (BIREME), the Scientific Electronic Library Online (Scielo), Web of Science, the Cumulative Index to Nursing and Allied Health Literature (Cinahl), the Education Resources Information Center (ERIC), and the multidisciplinary database (Scopus). National and international publications in English, available online and published from 2013 onwards were selected. A total of 1422 records were found in the searches, and a selection of 12 research articles including theses, dissertations, and scientific papers, were presented in the flowchart of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (Prisma) recommendations. The selected studies were organized in tables, presenting information such as number, author, year of publication, Brazilian region, study type, study objective, participants, theoretical framework, educational intervention goals, National Patient Safety Program theme addressed, course content, educational strategy, instructional resource, intervention duration, and outcome level according to the Kirkpatrick method, as well as the institution promoting the educational activity. Results: The Brazilian regions that published the most studies on educational activities for patient safety were the South and Southeast. The studies presented various methods, with experience reports being the most frequent. Regarding methodology, qualitative approach was the most utilized. The nursing team (nurses, technicians, and nursing assistants) was the predominant population in the studies. The main findings regarding the most utilized educational strategies were realistic simulation and problematization. The most addressed themes of the National Patient Safety Program were healthcare-associated infection and safety in prescription, medication use, and administration. Conclusions: This review allowed the identification of critical factors for the development and improvement of educational interventions related to patient safety, adherence to the main protocols of the National Patient Safety Program, as well as gaps in educational interventions regarding effective communication and the importance of evaluating trainings, as well as measuring their impact on healthcare.
Educational activities developed in Brazil for health professionals and graduates with a focus on patient safety: scoping review
Keywords: Profissionais de saúde; Atividades educacionais; Segurança do paciente; Serviços de saúde; Healthcare professionals; Educational activities; Patient safety; Healthcare services; CIENCIAS DA SAUDE